Growth conditions and survival kinetics during storage of Lactobacillus rhamnosus GG for the design of a sustainable probiotic whey-based beverage containing Costa Rican guava fruit pulp - Montero Zamora, Jéssica Pamela (2020)
The finding of economical and practical applications for milk whey is still a challenge for dairy industries. This paper presents information about the development of a probiotic–prebiotic beverage based on Lactobacillus rhamnosus GG (LGG) and Costa Rican guava (CRG) fruit pulp with industrial potential. First, a supplemented whey media was developed for LGG growth, and the whey-supplemented media was used for fermentation in bioreactors. LGG reached a maximum growth rate of 0.32 hr−1 after 48 hr of fermentation. The whey-grown probiotics were then mixed with CRG pulp to produce the probiotic–prebiotic beverage. The survival kinetics of LGG in the formulated drink was not affected by the addition of CRG pulp (P > 0.05), and the shelf-life of the inoculated beverage surpassed 40 days with a minimum population of 106 colony forming units (CFU)/mL. Properties as pH, fructose, glucose, sucrose, and proanthocyanidins (PACs) content exhibited a significant difference after storage time (P < 0.05). Finally, three different formulas of the beverage with different whey content were compared through sensory evaluation. The prototype with 50% whey content was one of the most valuable beverage formulas according to the organoleptic parameters, which remarks about the possibility of developing a probiotic whey-based beverage containing CRG pulp. Furthermore, this is the first report about CRG beverages as a probiotic vector.